0101 Developing Non-technical Skills Through Simulation: Designing A Course To Improve Patient Safety. (1st November 2014) - Stewart-Parker, Emmie; Martinou, Eirini; Galloway, Rob; Finn, Simon; Kalidasan, Varadarajan; Vig, Stella
Abstract : Background: Providing teaching on non-technical skills, or 'human factors', is of increasing interest to healthcare professionals, yet it is rarely universally taught. Teams continue to make human errors despite technical expertise and knowledge, compromising patient safety. Our aim was to design a one-day, multi-professional, multidisciplinary course to teach, practice and apply non-technical and team-working skills in emergency situations through simulated scenarios in a safe, open, environment. Methodology: To cater for different clinical settings, and the various teams therein operating, the course would provide a common teaching 'stem' of morning lectures, case studies and team-working exercises, with speciality themed afternoon simulated scenarios to practice these. So far, we have developed 'A-TEAMS: Advanced Teamworking in Emergency and Acute Medical Situations', set in the emergency department, and 'S-TEAMS' the surgical equivalent, set in theatre. During simulation, professionals stay within their normal role to keep the experience as realistic as possible. Teams are encouraged to focus on skills such as communication strategies, situational awareness and the use of prompts, eg checklists, to improve team-working. A thorough debrief with highly experienced senior clinicians follows. Results: Over 150 healthcare professionals have completed the course thus far. All participants felt the course had a clear structure and that learning objectives were explicit. 95% felt the scenarios had good or excellent relevance to clinical practice. 100% found the course useful and would recommend it to their colleagues. Longer-term data (up to 18 months post course completion) revealed 98% of participants had incorporated the non-technical skills learnt into clinical practice. Potential impact: There is a real demand and enthusiasm for developing non-technical skills within modern healthcare. A training course which includes simulation, focusing on human factors in a multiprofessional and multidisciplinary environment will improve not only team-working, but the culture in general and, ultimately, patient safety. References: Flin R, O'Connor P, Crichton M.' Safety at te Sharp End', First Ed, 2008, Ashgate Publishing Ltd Flin R, Maran N. 'Identifying and Training Non-technical Skills for Teams in Acute Medicine'. Quality and Safety in Healthcare 2004;3:i80–i84 Yule et al . 'Non technical skills for surgeons in the operating room: a review of literature'. Surgery 2006;39;6:140–149 Andersen et al . 'Identifying Non-technical Skills and Barriers for Improvement in Cardiac Arrest Teams'. Resuscitation 2010;81;6:695–702